'A southern college slipped from its geographical moorings': slavery at Princeton. (3rd April 2018) - Inniss, Lolita Buckner
ABSTRACT: While slave-owning students at Princeton rarely constituted a majority of students, they were often a large plurality of the students in the antebellum period. Because of Princeton's historic role in educating southerners, it has sometimes been referred to as the most southern of the Ivy League schools. So many students from the United States South enrolled at Princeton during the first several decades of the college that one observer wrote that one might take Princeton for a 'Southern college slipped from its geographical moorings.' This article explores the extent to which and whether Princeton behaved like a southern institution in its speech and actions concerning slavery and emancipation.